2011
DOI: 10.2298/sos1103343v
|View full text |Cite
|
Sign up to set email alerts
|

Solid state synthesis of extra phase-pure Li4Ti5O12 spinel

Abstract: Extra phase-pure Li4Ti5O12 spinel with particle sizes less than 500 nm was synthesized by solid state reaction of mechanochemicaly activated mixture of nano anatase and Li2CO3 for a very short annealing time, 4 h at 800°C. Structural and microstructural properties, the mechanism of solid state reaction between anatase and Li2CO3 as well as thermal stability of prepared spinel were investigated using XRPD, SEM and TG/DSC analysis. The mechanism of reaction implies decomposition of Li2CO3 below 250ºC, form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…After 100 cycles ( Figure 6(d)), the remaining capacities were 86% (rate C/10), 74% (rate 1C), and 75% (rate 10C) of capacity initial that were registered, corresponding to a specific capacity of 150 mAh/g, 111 mAh/g, and 100 mAh/g, respectively. We believe that the particles in nanosize shorten the pathway diffusion of lithium ions and encourage the performance of spinel Li 4 the previous studies which showed a specific capacity of 150 mAh/g in rate 1C and 100 mAh/g in rate 10C [9,11,15].…”
Section: Electrochemicalmentioning
confidence: 65%
See 1 more Smart Citation
“…After 100 cycles ( Figure 6(d)), the remaining capacities were 86% (rate C/10), 74% (rate 1C), and 75% (rate 10C) of capacity initial that were registered, corresponding to a specific capacity of 150 mAh/g, 111 mAh/g, and 100 mAh/g, respectively. We believe that the particles in nanosize shorten the pathway diffusion of lithium ions and encourage the performance of spinel Li 4 the previous studies which showed a specific capacity of 150 mAh/g in rate 1C and 100 mAh/g in rate 10C [9,11,15].…”
Section: Electrochemicalmentioning
confidence: 65%
“…Ti 5 O 12 through the formation of intermediate C-base centered orthorhombic Li 1.81 H 0.19 Ti 2 O 5 ⋅2H 2 O (LTH). The presence of LTH seems to be easily converted in Li 4 Ti 5 O 12phase at low temperature range (<700 ∘ C) compared to the same layered structure / -Li 2 TiO 3 , usually obtained in solid state reaction or hydrothermal process[15].…”
mentioning
confidence: 88%
“…The second weight loss is 16.44 wt.% at 450–710 °C, corresponding to a broad exothermic peak at 600–710 °C in the DSC curve, which corresponds well to the theoretical weight loss of CO 2 from Li 2 CO 3 (15.6 wt.%). Here, ball milling can decrease the temperature of CO 2 loss (<400 °C) 33,34 . Therefore, there are different reaction temperatures under different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying crystal structure and its change upon lithiation/delithiation was intensively studied by powder [12][13][14][15][16][17] and single crystal diffraction [18][19]. In the LTO unit cell (Li) 8a …”
Section: Accepted Manuscriptmentioning
confidence: 99%